A Contrapuntal and Spenglerian Approach to Misericordia. - Ullman, Pierre L. (Hispanic Review)
Presents a contrapuntal and Spenglerian approach to "Misericordia." Northrop Frye's modes of literary history; Explanation of the five phases; Example linking the hero with a symbol; Passages where the protagonist is defined in low mimetic terms; Why San Sebastian is symbologically unsuitable for two of the higher phases; Parallelism of the literal phase with the ironic mode; More.